Pengaruh Terapi Murrotal Al-Qur’an terhadap Pasien dengan Risiko Perilaku Kekerasan di Yayasan Aulia Rahma - Tarisya Cindy Natasya; Ardinata Ardinata; Sutrisno Sutrisno; Melly Santika (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
In 2021, the Ministry of Health and WHO estimated that mental disorders affect around 450 million people worldwide, with 2.5 million of them in Indonesia.Of that number, around 60% are patients at risk of violent behavior.Every year, more than 1.6 million people die from violence, especially men aged 15-44 years.Meanwhile, survivors often experience physical, sexual, reproductive trauma, and mental health disorders.This reflects the deteriorating mental health indicators of the community.This study aims to assess the effect of Al-Quran murrotal therapy on patients at risk of violent behavior at the Aulia Rahma Foundation, Bandar Lampung in 2024. The research method used is quantitative with an experimental design, using a pretest and posttest approach without a control group.The population of this study consisted of patients at risk of committing violent behavior at the Aulia Rahma Foundation in 2024, with a total of 12 patients.The research sample was taken using the total sampling technique, where the entire population was sampled, so that there were 12 respondents.Statistical analysis was carried out using the Wilcoxon non-parametric test. The results showed that before being given Al-Quran murrotal therapy, most respondents (83.3%) had a high risk of violent behavior.After therapy, most respondents (66.7%) showed a significant decrease in the risk of violent behavior.The Wilcoxon Signed Ranks Test statistical test produced a p-value of 0.003 which is smaller than 0.05, which indicates that Al-Quran murrotal therapy has an effect on reducing the risk of violent behavior in patients at the Aulia Rahma Foundation Bandar Lampung.This study is expected to encourage health institutions to provide education on the importance of Al-Quran murrotal therapy for patients at risk of committing violent behavior.